Kapasitas Antioksidan Ekstrak Buah Rukam (Flacourtia rukam) Menggunakan Metode Microwave Assisted Extraction (MAE) - Fadiyah, Inas; Lestari, Iin; Mahardika, Robby Gus (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Rukam fruit (Flacourtia rukam) is one of the species spread in Indonesia, specifically Bangka Island. Rukam has a higher phenolic ratio than guava (Psidium guajava). Phenolic compounds have a major role as antioxidants, while antioxidants have the ability to fight free radicals. Therefore a study was conducted to examine the application of secondary metabolites and antioxidant bioactivity of the Flacourtia rukam species using the Microwave Assisted Extraction method. Rukam fruit extract is obtained by using the Microwave Assisted Extraction (MAE) method. While for the antioxidant test using the DPPH method. The test results of antioxidant activity of rukam fruit extract with ethanol solvent were obtained with IC50 value 47.7022 ppm and in rukam fruit extract with acetone solvent IC50 33.1702 ppm obtained using this antioxidant antioxidant powder was very strong.